A comparison of families of children with autism spectrum disorders in family daily routines, service usage, and stress levels by regionality - McAuliffe, Tomomi; Vaz, Sharmila; Falkmer, Torbjorn; Cordier, Reinie (Informa Healthcare, 2017)
Purpose: To explore whether family routines, service usage, and stress levels in families of children with autism spectrum disorder differ as a function of regionality. Methods: Secondary analysis of data was undertaken from 535 surveys. Univariate and multivariate analyses were performed to investigate differences between families living in densely populated (DP) areas and less densely populated (LDP) areas. Results: Families living in LDP areas were found to: (1) have reduced employment hours (a two-parent household: Exp (B) = 3.48, p < .001, a single-parent household: Exp (B) = 3.32, p = .011); (2) travel greater distance to access medical facilities (Exp (B) = 1.27, p = .006); and (3) report less severe stress levels (Exp (B) = 0.22, p = .014). Conclusions: There were no differences in family routines; however, flexible employment opportunities and travel distance to medical services need to be considered in families living in LDP areas.